Production of Biofuel Crops in Florida: Sweet Sorghum - Wilfred Vermerris; Curtis Rainbolt; David L. Wright; Yoana C. Newman (EDIS)
This series of illustrated fact sheets introduces growers to several potential biofuel crops for Florida, with assessments of potential, description of biology, production, potential yields, production challenges and estimated costs, environmental concerns, and references. Published by the UF Department of Agronomy, December 2007.